2012
DOI: 10.1118/1.4769119
|View full text |Cite
|
Sign up to set email alerts
|

External beam pulsed low dose radiotherapy using volumetric modulated arc therapy: Planning and delivery

Abstract: Elekta linacs are capable of delivering reproducible and stable PLRT plans. A prospective clinical study employing PLRT is currently in development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The data showing ECRR1 staining in tumor sections (Figure 4B) were not conclusive, and future studies are being planned to determine the absolute delivery of CDDP to irradiated tumors using atomic absorption spectrophotometry(39,40).Previously published studies using PRT for recurrent glioblastoma have demonstrated that PRT is clinically feasible, and patients have tolerated PRT treatment well(11). Volumetric modulated arc radiotherapy (VMAT) reduces treatment delivery time significantly and a PRT plan can be delivered in approximately 50 minutes(42). However, this length of treatment may still represent a challenge for head and neck patients as they near the completion of their treatment when the…”
mentioning
confidence: 97%
“…The data showing ECRR1 staining in tumor sections (Figure 4B) were not conclusive, and future studies are being planned to determine the absolute delivery of CDDP to irradiated tumors using atomic absorption spectrophotometry(39,40).Previously published studies using PRT for recurrent glioblastoma have demonstrated that PRT is clinically feasible, and patients have tolerated PRT treatment well(11). Volumetric modulated arc radiotherapy (VMAT) reduces treatment delivery time significantly and a PRT plan can be delivered in approximately 50 minutes(42). However, this length of treatment may still represent a challenge for head and neck patients as they near the completion of their treatment when the…”
mentioning
confidence: 97%
“…Intensity‐modulated arc therapy is a desirable alternative to 3D CRT for LDR irradiation, offering the advantages of a uniform dose to the PTV per 20 cGy field and improved PTV conformity; Tyagi et al (13) have reported on VMAT planning and delivery of LDR brain cases using the Pinnacle 3 treatment planning system (Philips Radiation Oncology Systems, Fitchburg, WI) and Elekta linear accelerators (Elekta, Inc., Crawley, UK). At our institution to‐date, mARC has been used to administer a low‐dose‐rate (LDR) treatment to 17 patients.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that it is possible to use one or two intensity‐modulated arcs to deliver PLDR plans to achieve better target coverage and normal tissue sparing for treatment of complex tumors (9‐11) . The PLDR treatment of recurrent cancers using dynamic arc therapy delivers 0.2 Gy to the target per arc with a 3 min interval.…”
Section: Introductionmentioning
confidence: 99%
“…Rong et al (10) demonstrated that with special machine parameters, a tomotherapy plan could be delivered within the 3 min time interval to meet the PLDR treatment requirement with a 3 min interval between fields. Tyagi et al (11) showed that previously treated glioblastoma multiforme (GBM) cases could be replanned using volumetric‐modulated arc therapy (VMAT) with a single 160° arc to deliver 0.2 Gy pulses on the new Elekta accelerator (Elekta AB, Stockholm, Sweden). Ma et al (9) implemented the PLDR technique using the Varian RapidArc technique (Varian Medical Systems, Palo Alto, CA).…”
Section: Introductionmentioning
confidence: 99%